Biliary sequelae of endoscopic sphincterotomy. Issue 713 (March 1985) - Greenfield, C.; Cleland, P.; Dick, R.; Masters, S.; Summerfield, J. A.; Sherlock, S.
Abstract : Twenty five patients were reviewed a mean of 36 months after successful endoscopic sphincterotomy for the removal of bile duct stones. All the patients had improved symptomatically but 20% had episodes of mild abdominal pain and a similar number had elevated serum gamma glutamyltranspeptidase activities (up to 3 times normal). In 12 patients (50%) biliary gas was demonstrated indicating reflux of duodenal contents. Clinical cholangitis did not occur. Aspiration liver biopsy revealed mild portal tract fibrosis and inflammation in patients with biliary reflux. Biliary reflux was significantly associated with mild upper abdominal pain (P less than 0.05). This study has shown that mild abnormalities of biliary function persist after endoscopic sphincterotomy. The long term consequence of these changes is unclear.